The role of language in emotion: predictions from psychological constructionism - Lindquist, Kristen A.; MacCormack, Jennifer K.; Shablack, Holly (Frontiers in Psychology, 2015)
Common sense suggests that emotions are physical types that have little to do with the words we use to label them. Yet recent psychological constructionist accounts reveal that language is a fundamental element in emotion that is constitutive of both emotion experiences and perceptions. According to the psychological constructionist Conceptual Act Theory, an instance of emotion occurs when information from one’s body or other people’s bodies is made meaningful in light of the present situation using concept knowledge about emotion. The CAT suggests that language plays a role in emotion because language supports the conceptual knowledge used to make meaning of sensations from the body and world in a given context. In the present paper, we review evidence from developmental and cognitive science to reveal that language scaffolds concept knowledge in humans, helping humans to acquire abstract concepts such as emotion categories across the lifespan. Critically, language later helps individuals use concepts to make meaning of on-going sensory perceptions. Building on this evidence, we outline predictions from a psychological constructionist model of emotion in which language serves as the “glue” for emotion concept knowledge, binding concepts to embodied experiences and in turn shaping the ongoing processing of sensory information from the body and world to create emotional experiences and perceptions.